2009
DOI: 10.1021/jf900995d
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Dichlorvos and Omethoate Residues by O2 Plasma Treatment

Abstract: A practical, inexpensive, and green chemical process is greatly needed for degrading pesticides in food and environmental water. In this work, the impact of O(2) plasma treatment on reduction of dichlorvos (DDVP) and omethoate in maize was determined by gas chromatography (GC). The main plasma-induced degradation mechanisms were investigated through identification of intermediates or products during O(2) plasma treatment for DDVP and omethoate on solid surfaces by gas chromatography/mass spectrometry (GC/MS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Compound 3 (C3) with retention time 16.8 min could correspond to N-methyl-2-sulfanylacetamide through comparing its mass spectrum with that reported in a previous study (Bai et al, 2009). C3 had a molecular ion at m/z 105, which lose HSA to yield m/z 72 or lose HSCH 3 A to yield m/z 58.…”
Section: Identification Of Hmw Degradation Byproductsmentioning
confidence: 75%
See 1 more Smart Citation
“…Compound 3 (C3) with retention time 16.8 min could correspond to N-methyl-2-sulfanylacetamide through comparing its mass spectrum with that reported in a previous study (Bai et al, 2009). C3 had a molecular ion at m/z 105, which lose HSA to yield m/z 72 or lose HSCH 3 A to yield m/z 58.…”
Section: Identification Of Hmw Degradation Byproductsmentioning
confidence: 75%
“…The fragment ions at m/z 141 and 125 could originate from the loss of CH 3 A and CH 3 OA from the molecular ion, respectively. It has been reported that photo-and thermal-degradation of dimethoate would produce STMP (Andreozzi et al, 1999;Bai et al, 2009).…”
Section: Identification Of Hmw Degradation Byproductsmentioning
confidence: 99%
“…Recently, an inductively coupled plasma (ICP) source was employed for the degradation of dichlorvos and omethoate sprayed onto maize (Bai, Chen, Mu, Zhang, & Li, 2009;Bai, Chen, Yang, Guo, & Zhang, 2010). Heo et al (2014) investigated the efficacy of a dielectric barrier discharge (DBD) plasma for the degradation of pesticides on apples.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike microbiological decontamination, only a limited number of studies have demonstrated the successful degradation of pesticides by NTP. The degradation of Dichlorvos and Omethoate organophosphorus pesticides sprayed onto maize samples when treated with an inductively coupled radiofrequency NTP source operating in oxygen was studied by Bai, Chen, Mu, Zhang and Li [8]. Recently, Bai, Chen, Yang, Guo and Zhang [9] also demonstrated the successful degradation of dichlorvos pesticides coated on glass slides using the same inductively coupled plasma (ICP) source.…”
Section: Introductionmentioning
confidence: 99%